A SYSTEMATIC LITERATURE REVIEW PERAN STRATEGIS PEMASARAN DIGITAL DALAM MENINGKATKAN PENJUALAN PUPUK: SYSTEMATIC LITERATURE REVIEW THE STRATEGIC ROLE OF DIGITAL MARKETING IN INCREASING FERTILIZER SALES - Siregar, Diffri; Jhon Veri (Program Studi Ekonomi Syariah, 2024)
Advances in information and communication technology have had a major impact on various kinds of human life, including the economy and business. Digital transformation has conquered the production, distribution, marketing and consumption of goods and services. The type of research carried out is Systematic Literature Review. The research aims to examine the role of digital marketing strategies in increasing sales. There were 732 research findings found through the Google Scholar database, 170 findings were found to be in accordance with the concept of the specified criteria and from a total of 170 research findings, 14 research journals were found that were in accordance with the research concept, of these 14 journals there were 4 research findings that were excluded because they were summaries. from a thesis/thesis/dissertation obtained from the university's web repository and there is 1 journal that has the same title. So the total journals that are relevant to the keywords are 9 journals. The results of research questions 1 and 2 show that almost all journals use the same digital marketing strategy to increase sales. Keywords: Digital Marketing, Strategy, Systematic Literature Review